u'' - u = epsilon * t*u t>0, u(0) = 1, u'(0) = -1 Find the exact solution. I know we need to use the method of undetermined coefficients, but not sure how to make it work out properly. Any help would be great, thanks!
Follow Math Help Forum on Facebook and Google+
Originally Posted by 860Def u'' - u = epsilon * t*u t>0, u(0) = 1, u'(0) = -1 Find the exact solution. I know we need to use the method of undetermined coefficients, but not sure how to make it work out properly. Any help would be great, thanks! what you typed seems strange. what are you using * to mean? and what's epsilon doing there? is it just a constant?
sorry, i was just using the * to indicate multiplication. epsilon is also just a constant. so let's have epsilon = some constant a, then we'll have u'' - u = atu t>0, u(0) = 1, u'(0) = -1 hope that clears my question up a little bit.
View Tag Cloud